Colonization history of Mallorca Island by the European rabbit, Oryctolagus cuniculus, and the Iberian hare, Lepus granatensis (Lagomorpha: Leporidae). (13th March 2014) - Seixas, Fernando A.; Juste, Javier; Campos, Paula F.; Carneiro, Miguel; Ferrand, Nuno; Alves, Paulo C.; Melo‐Ferreira, José
<x xml:space="preserve">Abstract</x> The Mediterranean islands have a long history of human‐mediated introductions resulting in frequent replacements of their fauna and flora. Although these histories are sometimes well documented or may be inferred from paleontological studies, the use of phylogenetic and population genetic reconstruction methods provides a complementary perspective for answering questions related to the history of insular species. In the present study, we infer the colonization history of Mallorca (Balearic Islands) by the European rabbit (Oryctolagus cuniculus) and the Iberian hare (Lepus granatensis) using sequence variation of the mitochondrial DNA control region from continental and insular specimens (total of 489 sequences). Additionally, the taxonomic identity of Mallorcan L. granatensis was confirmed using a diagnostic nuclear marker. For both Mallorcan rabbits and hares, genetic diversity was comparable to the continental populations, suggesting the introduction of multiple lineages. Two Mallorcan haplogroups were found in hares, which likely correspond to two introduction events. Rabbits from Mallorca were identified as belonging to the subspecies Oryctolagus cuniculus cuniculus, and may have been originated both from Iberian and French populations. The molecular estimates of the timing of the colonization events of the Mallorcan lagomorphs are consistent with human‐mediated introductions by early settlers on the islands. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 748–760.